Shimmer and whisper - Stok, Witold (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The author of the article, one of the acclaimed Polish cinematographers, describes his practical eforts involved in making two short documentary films on Holocaust directed by him. The first one, Sonderzug (1978), was based on Stok’s idea to recreate his first emotional reaction to the landscape around Treblinka in the film that lasts 9 minutes, as long as the way of the Jews from the ramp to their end in the death camp. The other film, Prayer (1981), is the portrayal of a Japanese Buddhist monk praying at the site of the former Auschwitz-Birkenau concentration camp. The formal inspiration of the film came from Japanese visual art.